Development and application of power head for CBM vehicle mounted drilling rig - Liu, Qi (E3S web of conferences, 2024)
In order to meet the construction needs of surface coalbed methane extraction holes, cable holes, and mine surface rescue holes, a multifunctional power head suitable for coalbed methane vehicle mounted drilling rigs has been developed. The power head adopts a dual speed hydraulic motor to drive the spindle rotation through a first gear reduction, with a compact structure, high transmission efficiency, large spindle diameter, wide range of speed and torque adjustment, and spindle braking function. It can be applied to various drilling processes such as air down the hole hammer, air lift reverse circulation, and directional drilling. On site tests have shown that the power head has high capacity, efficiency, comprehensive functions, and is easy to operate, providing equipment support for efficient and safe drilling construction.